Primär- und Sekundärprävention des Multiplen Myeloms - Cordas dos Santos, David; Erickson, Nicole; Gerland, Lars; Jundt, Franziska; Theurich, Sebastian (DMW - Deutsche Medizinische Wochenschrift, 2020)
Lifestyle factors such as diet, physical activity and exposure to noxious agents are modifiable factors that have a significant impact on the state of health and life expectancy of humans. The following article is intended to provide an overview of current knowledge on the influence of these lifestyle factors on the development and progression of multiple myeloma and is dedicated to the question of the extent to which prevention strategies can be usefully applied.
Keywords: Multiples Myelom; Adipositas; Ernährungstherapie; Bewegungstherapie